1967
DOI: 10.1017/s0021859600018633
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitrogen and irrigation on timothy (Phleum pratense) grown for production of seed: II. Reproductive growth and yield of seed

Abstract: The first part of this paper (Lambert, 1967) described the purpose and layout of the experiment, and presented data on the vegetative growth of S. 48 timothy at a low plant density (30 cm x 30 cm square pattern) for production of seed. The treatments involved were (a) irrigation to field capacity for a period from about 1 week before initiation of inflorescences until 2 weeks before harvest, except for periods of profuse an thesis, and (6) no irrigation; these treatments were applied at three levels of nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Lambert (1967) found that irrigation increased the proportion of heavy seed in timothy (Phleum pretense L.) and Chynoweth et al (2012) demonstrated that seed yield increases resulting from irrigation in perennial ryegrass were associated with increases in seed weight. Rowarth et al (1997) did not observe differences in seed weight from seed harvested from water-stressed and non-stressed perennial ryegrass plants grown under greenhouse conditions.…”
Section: Components Of Seed Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Lambert (1967) found that irrigation increased the proportion of heavy seed in timothy (Phleum pretense L.) and Chynoweth et al (2012) demonstrated that seed yield increases resulting from irrigation in perennial ryegrass were associated with increases in seed weight. Rowarth et al (1997) did not observe differences in seed weight from seed harvested from water-stressed and non-stressed perennial ryegrass plants grown under greenhouse conditions.…”
Section: Components Of Seed Yieldmentioning
confidence: 99%
“…Later senescence of the irrigated stands of perennial ryegrass may have led to increased seed weight as a result of a longer seed fill period. Delayed harvest has been reported in irrigated stands of timothy (Lambert, 1967) and perennial ryegrass (Hebblethwaite, 1977).…”
Section: Components Of Seed Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…1965;Lambert, 1967). Hebblethwaite (1977) found that irrigation of S23 perennial ryegrass increased seed yield by up to 52% but the magnitude of the response depended largely on the amount of rainfall during the experimental year.…”
mentioning
confidence: 99%
“…The seed yields of herbage species respond to nitrogen (N) application (Evans, 1954;Roberts, 1966;Hebblethwaite and Ivins, 1977) and to irrigation (Rampton. 1965;Lambert, 1967). Hebblethwaite (1977) found that irrigation of S23 perennial ryegrass increased seed yield by up to 52% but the magnitude of the response depended largely on the amount of rainfall during the experimental year.…”
mentioning
confidence: 99%